A numerical model of the behavior of the resistance to compression in prisms of solid masonry. (November 2019) - Afanador García, N; Farelo Alvarez, K A; Calderon, F
Abstract: This research work presents an experimental and numerical analysis of three-dimensional behavior to the compression of masonry prisms with solid brick, in pieces built-in artisanal ovens used in the municipality of Ocaña, Colombia, with the objective to determining deterministically the resistance to uniaxial compression and determine numerical models for structural design purposes. The experimental methodology consisted of determining statistically for solid clay brick units, the initial rate of absorption, final absorption, rupture modulus and resistance to uniaxial compression, and in masonry prisms, to uniaxial compression resistance and modulus of elasticity. The behavior observed in the uniaxial compression test in masonry prisms were validated in a commercial code of finite element modeling. The efficiency of the model makes it possible to predict the uniaxial compressive strength of masonry prisms in solid bricks built in artisan ovens. Allowing to reduce the number of tests in the future and perform probabilistic analysis.